Quantifying the relative importance of direct and indirect biophysical effects of deforestation on surface temperature and teleconnections (2018)
In this study, the authors linearize the surface energy budget equation that disentangles indirect effects (resulting from changes in downward shortwave and longwave radiation and air temperature) from direct biophysical effects (resulting from changes in surface albedo, evapotranspiration, and roughness length) of deforestation on land surface temperature. This formulation is applied to idealized deforestation simulations from two climate models and to realistic land-use and land-cover change (LULCC) simulations from 11 models, and the contribution of each underlying mechanism to surface temperature change is quantified. It is found that the boreal region experiences dominant indirect effects and the tropics experience dominant direct effects in all seasons in idealized deforestation simulations. The temperate region response differs in the two models. However, five out of seven models in response to realistic historical LULCC show a dominance of indirect effects in the temperate region. In response to future LULCC, three out of four models confirm the dominance of direct effects in the tropical region. It is found that indirect effects are always largely attributable to air temperature feedback and direct effects are essentially driven by changes in roughness length in both idealized and realistic simulations. Furthermore, teleconnections are shown to exist between deforested regions and the rest of the world, associated with the indirect effects. The study also shows that the partitioning between direct and indirect effects is highly model dependent, which may explain part of the intermodel spread found in previous studies comparing the total biophysical effects across models.